Vitamin D and Autoimmune Rheumatic Diseases - Lambros Athanassiou; Ifigenia Kostoglou-Athanassiou; Michael Koutsilieris; Yehuda Shoenfeld (Biomolecules, 2023)
Vitamin D is a steroid hormone with potent immune-modulating properties. It has been shown to stimulate innate immunity and induce immune tolerance. Extensive research efforts have shown that vitamin D deficiency may be related to the development of autoimmune diseases. Vitamin D deficiency has been observed in patients with rheumatoid arthritis (RA) and has been shown to be inversely related to disease activity. Moreover, vitamin D deficiency may be implicated in the pathogenesis of the disease. Vitamin D deficiency has also been observed in patients with systemic lupus erythematosus (SLE). It has been found to be inversely related to disease activity and renal involvement. In addition, vitamin D receptor polymorphisms have been studied in SLE. Vitamin D levels have been studied in patients with Sjogren’s syndrome, and vitamin D deficiency may be related to neuropathy and the development of lymphoma in the context of Sjogren’s syndrome. Vitamin D deficiency has been observed in ankylosing spondylitis, psoriatic arthritis (PsA), and idiopathic inflammatory myopathies. Vitamin D deficiency has also been observed in systemic sclerosis. Vitamin D deficiency may be implicated in the pathogenesis of autoimmunity, and it may be administered to prevent autoimmune disease and reduce pain in the context of autoimmune rheumatic disorders.